Where Is Europe? The Contribution of the Portuguese TV to the Coverage of the 2019 Elections to the European Parliament - Bonacho, Fernanda (2020)
The 2019 elections to the European Parliament (EP) were held in a climate of political unrest. Despite the impact and legislative importance of the EU governance upon our lives, a significant body of research has argued that so far there has not been a committed European news agenda focused on fostering citizen engagement with EU affairs so as to build a sense of Europeanness or a Europeanized discursive public sphere. The primary goal of our study was therefore to evaluate the role of the Portuguese television in informing the public and contextualizing the issues posed by the run-up to the EP election and the underlying process of the European construction. In Portugal, television remains a privileged medium for citizens to access information. Given that prime-time TV news bulletins manage to reach the highest audience ratings when compared to other information programmes, it is our aim to analyse RTP1, SIC and TVI news bulletins between 13-26 May – the period of the electoral campaign. A critical discourse analysis (combining quantitative and qualitative methods) will be followed in order to assess the newsworthiness of Europe -where is Europe? - and the interconnectedness between systems of representation, identity building and participatory citizenship.